THE AFFECTIVE BODY: PLATFORMED PRESENCE AND VIRTUAL EMBODIMENT IN THE POPULIST POLITICS OF NARENDRA MODI - Bhattacharya, Laboni (AoIR Selected Papers of Internet Research, 2021)
Political theory agrees that the charismatic leader’s cult of personality is a cornerstone of populist politics, with an increasingly distrustful, contentious, and internally divided society seeing the leader as the embodiment of the popular will more viscerally than the electoral process allows (Laclau 2005). The power of the hypermasculine leader persists in the digital age where populists exert authoritarian control over media narratives and infrastructures, as feminist critiques of the iconography of statesmen like Putin, Erdogan and Duterte demonstrate (Chavez and Pacheo 2020). Yet this brand of strongman politics is discursively co-produced by the leader’s physical presence; my presentation argues in contrast that Indian PM Narendra’s Modi’s affective body is animated by its persistent digitization, virtualization, and absence of liveness. Modi’s populism is driven by his appeal as a technocrat, a man accessible to the people via hologram, Twitter, exclusive apps, 3D modelled YouTube videos, and other digitally enabled forms of disembodied representation which create a “fantasy of unmediated access” (Govil and Baishya 2018). When Modi appears in public to perform yoga or lay a silver brick in the foundations of a temple, his corporeal form is one iteration of his virtualized, mediated persona. Modi’s independence from the demands of embodiment is made possible by his substantive digital presence. The experiential intensity and interactivity of social media creates what I term “platform affect”, which mobilizes affective discourses like nationalism to material effect, such as drawing large crowds galvanized by a sense of intimacy with Modi’s virtual and physical person.